2015
DOI: 10.1097/md.0000000000000895
|View full text |Cite
|
Sign up to set email alerts
|

Association of CYP1A1 and GSTM1 Polymorphisms With Oral Cancer Susceptibility

Abstract: Our meta-analysis was aimed to evaluate the association of CYP1A1 and glutathione-S-transferase M1 (GSTM1) polymorphisms with oral cancer susceptibility.The related articles were searched in PubMed, Embase, and CNKI databases. Fifty eligible studies were included in our meta-analysis. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate the relationship of CYP1A1 (rs4646903 and rs1048943) and GSTM1 polymorphisms with oral cancer risk. A random-effects model or fixed-effects model was emp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 63 publications
(43 reference statements)
1
11
0
Order By: Relevance
“…We applied ETMA to summary statistics from previous meta-analysis [ 27 , 30 , 35 ] (detailed information is presented in Methods). Table 4 shows the summary results of real data analysis (the detailed calculation process using the etma package is shown in S2 Text ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied ETMA to summary statistics from previous meta-analysis [ 27 , 30 , 35 ] (detailed information is presented in Methods). Table 4 shows the summary results of real data analysis (the detailed calculation process using the etma package is shown in S2 Text ).…”
Section: Resultsmentioning
confidence: 99%
“…This pathway also involves the GST family. We used the data from a meta-analysis of approximately 50 studies investigating the association between CYP1A1/GSTM1 and oral cancer [ 30 ] and selected the studies describing the genotypes of both GSTM1 and CYP1A1 rs4646903. This filter left 13 studies in our real data analysis (the detailed data are shown in S2 Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Ethnicity may be important factors in determining susceptibility to oral cancer for M1 and T1 alleles (Zhao et al, 2014;Liu et al, 2015). In a meta-analysis, M1 null genotype was found as risk factor for oral neoplasm in Asian but not Caucasians (Zhao et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…[38][39][40][41] Several phenotypes involved in carcinogen metabolism have been linked to HNC risk, though results have not always been in agreement. [42][43][44] As a consequence, extrapolations of results of individual studies to other populations cannot be made without further evaluation.…”
Section: Discussionmentioning
confidence: 99%